2023
DOI: 10.1002/ijc.34748
|View full text |Cite|
|
Sign up to set email alerts
|

Real‐world treatment patterns for palbociclib plus an aromatase inhibitor, or an aromatase inhibitor alone, for patients with metastatic breast cancer in the Flatiron Database

Hope S. Rugo,
Xianchen Liu,
Benjamin Li
et al.

Abstract: There are limited real‐world comparative effectiveness data for palbociclib plus an aromatase inhibitor (AI) as a first‐line (1L) treatment examining endpoints that require long term follow‐up and post 1L progression. The Flatiron Health Analytic Database was used to characterize treatment and dosing patterns in patients with hormone receptor‐positive/human epidermal growth factor 2‐negative (HR+/HER2−) metastatic breast cancer (mBC) receiving palbociclib plus an AI vs an AI alone in routine US clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Progression free survival compared to real world studies. In recent years, a handful of studies have established the benefits of CDK 4/6i in a real-world population compared to AI monotherapy [21,22]. A small retrospective study found 140 patients receiving CDK 4/6i treatment between 2014 and 2019 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Progression free survival compared to real world studies. In recent years, a handful of studies have established the benefits of CDK 4/6i in a real-world population compared to AI monotherapy [21,22]. A small retrospective study found 140 patients receiving CDK 4/6i treatment between 2014 and 2019 [23].…”
Section: Discussionmentioning
confidence: 99%